6-Chloro-3'-nitroflavone is a potent ligand for the benzodiazepine binding site of the GABA(A) receptor devoid of intrinsic activity - Viola, Haydee Ana Maria (2000)
6-Chloro-3'-nitroflavone integrates a list of nearly 70 flavone derivatives synthesized in our laboratories. The effects of 6-chloro-3'- nitroflavone on the benzodiazepine binding sites (BDZ-BSs) of the GABA(A) receptor were examined in vitro and in vivo. 6-Chloro-3'-nitroflavone inhibited the [3H]flunitrazepam ([3H]FNZ) binding to rat cerebral cortex membranes with a K(i) of 6.68 nM and the addition of GABA to extensively washed membranes did not modify its affinity for the BDZ-BSs (GABA-shift = 1. 16 ± 0.12). The binding assays performed in rat striatal and cerebellar brain membranes showed that this compound has similar affinity to different populations of BDZ-BSs. Electrophysiological experiments revealed that 6- chloro-3'-nitroflavone did not affect GABA(A)-receptors (GABA(A)-Rs) responses recorded in Xenopus oocytes expressing α1β2γ(2s) subunits, but blocked the potentiation exerted by diazepam (DZ) on GABA-activated chloride currents. In vivo experiments showed that 6-chloro-3'-nitroflavone did not possess anxiolytic, anticonvulsant, sedative, myorelaxant actions in mice or amnestic effects in rats; however, 6-chloro-3'-nitroflavone antagonized diazepam-induced antianxiety action, anticonvulsion, short-term, and long- term amnesia and motor incoordination. These biochemical, electrophysiological, and pharmacological results suggest that 6-chloro-3'- nitroflavone behaves as an antagonist of the BDZ-BSs.